ANALISIS PENERAPAN PRINSIP GOOD GOVERNANCE: EFEKTIVITAS PELAYANAN PENGADUAN MASYARAKAT DI SEKRETARIAT JENDERAL DPR REPUBLIK INDONESIA - Luthfi Nabilah Ailen; Adinda Maryam; Salman Paris Harahap (MAGISTRA Law Review, 2025)
Public service is a form of realization in conducting government administration. In this case, the public complaint service carried out by the Secretariat General of the DPR RI as a support for the DPR RI institution has tried to carry out its duties as much as possible. However, it cannot be denied that the condition of the complaint service certainly has obstacles or challenges in implementing and achieving effectiveness according to the principles of good governance. Therefore, the purpose of this research is to find out the extent to which the conditions of public complaints services have been carried out, see the effectiveness in accordance with the principles of good governance, and evaluate any challenges that become obstacles in realizing the principles of good governance. This research uses an empirical juridical method with a socio legal research approach conducted at the Public Complaints Section at the Secretariat General of the DPR RI, and obtains primary and secondary data to be analyzed with a qualitative descriptive method. The results and discussion show that the current governance condition of the implementation of public complaints services has been running well according to the legal basis that regulates it, its effectiveness with the principles of good governance has also been realized even though through several challenges, but these challenges become a form of evaluation for future service progress to be more optimal.